A Big Win in Smalltown: Demanding Dignity in an Era of Neoliberal Austerity - Vachon, Todd E. (Qualitative Sociology Review, 2018)
This article explores the concepts of dignity at work and worker voice in the public workplace during a period of surging neoliberal austerity intended to reduce taxes, government regulations, and public services. I ask how the changing landscape of public employment in the neoliberal era has created new and exacerbated existing threats to dignity at work and how workers have responded to such threats. The question is answered by exploring how and why an unlikely group of workers in Smalltown chose to use their collective voice on the job to organize a union. Using ethnographic methods, I am able to look at the strategies of public workers coping with a changing work environment in real time. The case of Smalltown offers a window into the interplay of the global and the local by examining how macro-level neoliberal forces can shape workers’ micro-level responses to attacks on their dignity at work. The findings reveal how neoliberal attacks on public workers in particular settings can trigger collective responses that confront not merely austerity but other threats to dignity as well. This study informs our understanding of dignity at work and worker resistance in the post-Great Recession economy.